Studi Mix Methods untuk Mengetahui Integrasi TPACK dalam Proses Pembelajaran Siswa Sekolah Dasar - Siti Ni'matul Fitriyah; Eddy Sutadji; Radeni Sukma Indra Dewi; Shirly Rizki Kusumaningrum (Postgraduate, University of Mataram, 2024)
The Technological Pedagogical and Content Knowledge (TPACK) framework offers guidance for teachers seeking to address technology integration in classroom learning. This study aims to assess the TPACK proficiency levels among elementary school teachers. This study involved teachers from SDN Sumbersari 03 in Malang City as participants using a mixed-methods approach with a sequential explanatory design. Quantitative data were initially gathered through self-report measures, followed by analysis utilizing descriptive and inferential statistics. Subsequently, qualitative data were collected through interviews and observations, with analysis conducted using the interactive model proposed by Miles and Huberman. The results of this study showed that there was no difference in the TPACK perceptions of primary school teachers based on gender (p-value > 0.05). However, there is an influence between age and tenure on teachers' TPACK ability (p-value < 0.05). Overall, the teachers have a good mastery of TPACK. However, there are some areas that need to be improved, especially in terms of technology mastery (TK, TCK, and TPACK). The highest mean score in the CK and PK domains was 4.875 and the lowest score in the TPACK domain was 4.55. The findings also indicate no significant difference in TPACK perceptions among elementary school teachers based on gender. However, age and tenure were found to influence teachers' TPACK abilities. Overall, teachers demonstrated a good level of mastery in TPACK. Nonetheless, specific areas, particularly technology mastery (TK, TCK, and TPACK), require improvement.